Angkor Wat: an introduction. (7th December 2015) - Fletcher, Roland; Evans, Damian; Pottier, Christophe; Rachna, Chhay
Abstract: Abstract : The temple of Angkor Wat, visited annually by tens of thousands of tourists, is without question one of the great archaeological sites of mainland Southeast Asia. Less obvious to the casual visitor is that it was but a single element in a large dispersed city. The papers in this special section demonstrate how recent research using LiDAR, ground-penetrating radar and targeted excavation have transformed our understanding of Angkor Wat and its surroundings.